Implementación de un entorno virtual en la plataforma de Moodle para los docentes de la asignatura de estudios sociales del primer año de bachillerato del colegio San Francisco de Asís de la ciudad de Loja periodo 2013 – 2014 - Castillo Roa, Jose Luis (2016)
The use of information technology and communication in the Ecuadorian educational process is very limited, and therefore, this research project grade is aimed at implementing a virtual environment, such as interactive teaching resource to optimize the teaching - learning process in the subject of Social Studies first year of high school of the Education Unit of St. Francis of Assisi the city of Loja. This project focused on gathering and grouping the most relevant information so that data collection techniques used; To carry out the virtual environment, methodology & T OLL Galvis was used because meets the phases of analysis, design, development, evaluation, administration. Finally it was considered that developed the virtual environment permitted to link teachers and students as teaching support material for teaching - learning.